THE MARKET OF VEGETABLES FROM ROMANIA - APOSTU (DASCALU), Ionica (Economics of Agriculture, 2012)
The market of the Romanian agriculture products is chaotic, at the disposal of occasional merchants who speculate the possibilities of negotiation. This is the belief of the agricultural farmers of Romania. There are also speculated the lack of information as well as of the market advice. The lack of a legislation regarding the market of the agricultural products harms the farmers and encourages the illicit transactions. The farmers need possibilities of storing the production for negotiating the terms of marketing, the appearance of an organism for settling the relationship between request and offer for getting possibilities of capitalisation the production, as well as the future request of the market, for structuring their activity.